EAACI Molecular Allergology User's Guide. (11th June 2016) - Matricardi, P. M.; Kleine‐Tebbe, J.; Hoffmann, H. J.; Valenta, R.; Hilger, C.; Hofmaier, S.; Aalberse, R. C.; Agache, I.; Asero, R.; Ballmer‐Weber, B.; Barber, D.; Beyer, K.; et al.
Abstract: The availability of allergen molecules ('components') from several protein families has advanced our understanding of immunoglobulin E (IgE)‐mediated responses and enabled 'component‐resolved diagnosis' (CRD). The European Academy of Allergy and Clinical Immunology (EAACI) Molecular Allergology User's Guide (MAUG) provides comprehensive information on important allergens and describes the diagnostic options using CRD. Part A of the EAACI MAUG introduces allergen molecules, families, composition of extracts, databases, and diagnostic IgE, skin, and basophil tests. Singleplex and multiplex IgE assays with components improve both sensitivity for low‐abundance allergens and analytical specificity; IgE to individual allergens can yield information on clinical risks and distinguish cross‐reactivity from true primary sensitization. Part B discusses the clinical and molecular aspects of IgE‐mediated allergies to foods (including nuts, seeds, legumes, fruits, vegetables, cereal grains, milk, egg, meat, fish, and shellfish), inhalants (pollen, mold spores, mites, and animal dander), and Hymenoptera venom. Diagnostic algorithms and short case histories provide useful information for the clinical workup of allergic individuals targeted for CRD. Part C covers protein families containing ubiquitous, highly cross‐reactive panallergens from plant (lipid transfer proteins, polcalcins, PR‐10, profilins) and animal sources (lipocalins, parvalbumins, serum albumins, tropomyosins) and explains their diagnostic and clinical utility. Part D lists 100 important allergen molecules. In conclusion, IgE‐mediated reactions and allergic diseases, including allergic rhinoconjunctivitis, asthma, food reactions, and insect sting reactions, are discussed from a novel molecular perspective. The EAACI MAUG documents the rapid progression of molecular allergology from basic research to its integration into clinical practice, a quantum leap in the management of allergic patients.